Cow Dung Extract Inhibited Testosterone-Induced Benign Prostatic Hyperplasia (BPH) In Wistar Rats - Ajala, Olusegun S.; Adelekan, Titilope A.; Lamina, Afolabi S. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Animal dungs could be a veritable source of steroidal and/or non-steroidal 5? -reductase inhibitory anti-Benign Prostatic Hyperplasia (BPH) drugs. A methanol cow dung extract was therefore evaluated for its possible anti-BPH act ivity in vivo in rats. Male Wistar albino rats (48) were randomly sorted into six groups of 8. Prostate hyperplasia was induced in five of the groups by a 30- day daily subcutaneous administration of 3mg/kg testosterone. One (the control) of these BPH model groups received a testosterone only regimen while each of the remaining four received orally the BPH-inducing testosterone concurrently with one of 100mg/kg, 200mg/kg, 400mg/kg cow dung extract or 10mg/kg finasteride (standard reference). The sixth group (bland) received olive oil and 2% tween 20, the respective vehicles for the hyperplasia-inducing subcutaneous testosterone and the remedial oral extract/finasteride. Each animal was sacrificed on the 31st day, its prostate removed, weighed and prostate weight/100g animal subsequently determined.Testosterone was found to produce a highly significant increase (p < 0.0001) in prostate weight after a 30-day daily administration. Likewise, cow dung extract was found to cause a highly significant inhibition (p < 0.0001) of the testosteroneinduced prostate weight increase at 100mg/kg, 200mg/kg and 400mg/kg doses each. Cow dung could therefore be explored as a promising source of new 5?-reductase-inhibiting anti-BPH compounds.